Reliability of an Innovative Slab Shear versus Microtensile Bond Strength Test: Mechanical and Finite Element Analysis - Abo-Alazm, Emad Abd Elfatah; Abdou, Ahmed; Hassouneh, Layla; Safy, Rehab Khalil (European Journal of Dentistry, 2023)
Objective The aim of this study was to evaluate the efficiency of slab shear bond strength test (Slab_SBS) versus the microtensile in evaluation of the bond strength of different substrates.Materials and Methods Forty-eight extracted caries-free human third molars were utilized for teeth specimens' preparation. After flattening of all molars' occlusal table, the specimens were divided into two groups based on the type of utilized restorative material: nanohybrid resin composite and resin-modified glass ionomer (RMGI). Each group was further subdivided into three subgroups according to the subsequently applied bond strength test and specimen width; microtensile bond strength test (μTBS), Slab_SBS [2 mm] and Slab_SBS [3 mm]. Both testing methods were additionally applied on CAD/CAM specimens, nanohybrid resin composite blocks (composite-to-composite), and ceramic blocks (ceramic-to-ceramic). CAD/CAM specimens were prepared and cemented and then sectioned and subdivided as followed for teeth specimens' preparation. Pretest failures (PTF), bond strength, and failure mode of each specimen were recorded. Representative three-dimensional (3D) finite element analysis (FEA) models were developed to simulate μTBS and Slab_SBS specimens. Data were statistically analyzed using Shapiro–Wilk test and Weibull analysis.Results Pretest failures were only noted in the μTBS subgroups. Slab_SBS provided comparable bond strength to the μTBS of all substrates with adhesive mode of failure.Conclusion Slab_SBS is easier to prepare with consistent and predictable outcome with no pretest failures during specimen preparation and better stress distribution.
Keywords: slab shear; microtensile; pretest failure; bond strength test; failure mode; finite element analysis